Editorial - Ramazan MAMMADOV (International Journal of Secondary Metabolite)
Distinguished Readers, We have created our journal named "International Journal of Secondary Metabolites". We published the first volume and issue. In the first issue, there is a summary of the symposium of ISSMET2014 that we had started at Pamukkale University in 2011 (Turkey) and continued at Moscow (Russia) in 2014. The journal will be published twice a year. The journal can be accessed via the internet. Why was it necessary to publish this journal? Primarily, in recent years, increase in the interest of scientists in the struggle against disease to the plant sources caused to the acceleration of the work on the secondary metabolites (secondary metabolites). Thus, the subject has been current and extremely popular. Although there are journals with different names covering similar topics, they do not meet the needs adequately. Therefore, "International Journal of Secondary Metabolites" journal was created by our group. There are referee groups who have the work experience in the field of secondary metabolites and are devoted to working with self-sacrifice in publishing each issue of the journal. On the other hand, the people who are recognized in the field will be asked to help in the assessment of the articles submitted to the journal. It is expected that this journal will become better in many ways within a short time with your contributions. With all of respect and love.   Saygıdeğer okurlar, “International Journal of Secondary Metabolite” adlı dergimizi  oluşturduk, ilk cilt ve sayısının yayınladık. İlk sayıda 2011 yılında Pamukkale Üniversitesinde (Türkiye) başlatmış olduğumuz ve ikincisini Moskova’da (Rusya) yapmış olduğumuz ISSMET2014 sempozyum’unun özetlerini yeralmaktadır. Dergi şimdilik yılda iki kez yayınlanacaktır. Dergiye internet üzerinden ulaşılabilmektedir.    Dergiye neden ihtiyaç duyuldu? Öncelikle, son yıllarda hastalıklara karşı mücadelede bilim adamlarının bitkisel kaynaklara yönelmesi ikincil metabolitler (sekonder metabolitler) üzerinde yapılan çalışmaların hızlanmasına neden olmuştur. Böylece konu son derece güncel ve popüler olmuştur. Her ne kadar bu konularda farklı isimler altında dergiler var olsa da ihtiyaçları yeterince karşılamamaktadır. Bundan dolayı “International Journal of Secondary Metabolite” dergisi grubumuz tarafından oluşturulmuştur. Derginin ikincil metabolitler alanında çalışma deneyimine sahip ve kendini derginin her bir sayısının çıkarılmasında özveri ile çalışmaya adamış olan bir hakem grubu vardır. Bunun dışında dergiye gönderilen makalelerin okunmasında alanında tanınmış olan kişilerden de hakemlik yardımları istenecektir. Umarız ki, sözkonusu dergi sizlerin katkılarınızla kısa zaman içinde daha iyi yerlere gelebilecektir. Hepinize saygılar ve sevgiler.   Prof. Dr. Ramazan MAMMADOV Editor